Pengaruh Komunikasi dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Pendidikan - As, Emilailan; Muhtar, Entang Adhy; Wahyudi, Heri (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The problem of employee performance at the Malinau Regency Education Office is a decline in performance in the last 3 years, allegedly related to ineffective communication and a work environment that is not fully conducive. This study aims to analyse the effect of communication and environment on employee performance. The theories used in this study, namely Communication variables (VX1), Work Environment Variables (VX2), and Y Performance Variables. This study uses a quantitative approach with a statistical test method using multiple regression hypotheses (T test and F test), with the Independent variables namely VX1 (Communication Effect), VX2 (Work Environment Effect), and Denpenden Variable Y (Performance). The instrument used is a questionnaire. The population totalled 66 employees with saturated sampling technique. The results of descriptive analysis, communication variables (X1) based on the classification are included in the good category (B), but the horizontal communication indicator 64.24 based on the classification is included in the less good category (KB) and is below the percent value of the average score of communication variables. As for the work environment variable (X2), the work environment is included in the less good category (KB). While the performance variable (Y) is included in the less good category (KB). There is a positive influence between communication on employee performance based on the calculation of Thitung 3.892 greater than Ttable 1.669 and the influence of the Work Environment on employee performance obtained Thitung value 6.054 greater than Ttable 1.669. Based on the f test research simultaneously shows the influence of communication and work environment on performance obtained Fcount value 53.524 greater than Ftable 3.145. The coefficient of determination shows that the independent variables (VX1 and VX2) are 61.8% and the remaining 38.2% is explained by other variables not examined in this study.